Evidence and implication of interventions across various socioecological levels to address HIV testing uptake among men who have sex with men in the United States: A systematic review. (June 2022) - Wang, Ying; Mitchell, Jason; Liu, Yu
Objectives: Strengthening HIV testing uptake is critical to curtail the HIV epidemics among men who have sex with men in the United States. Despite the implementation of various interventions to promote HIV testing among men who have sex with men, few aggregated evidence is presented to reflect the "lessons learned" and inform future directions. The objective of this systematic review is to comprehensively summarize published studies that described, tested, and evaluated outcomes (e.g. efficacy, effectiveness, acceptability, feasibility and/or qualitative opinions) associated with an HIV testing intervention and identify gaps as well as opportunities to inform the design and implementation of future interventions to enhance HIV testing uptake among men who have sex with men in the United States. Methods: We followed the PRISMA guidelines and conducted a systematic review of articles (published by 23 July 2021) by searching multiple databases (PubMed, MEDLINE, Web of Science and PsycINFO). Results: Among the total number of 3505 articles found through multiple databases, 56 papers were included into the review. Interventional modules that demonstrated acceptability, feasibility and efficacy to improve HIV testing uptake among men who have sex with men include: HIV self-testing, interpersonal-level (e.g. peer-led, couple-based) interventions, personalized interventions and technology-based interventions (e.g. mHealth). Aggregated evidence also reflects the lack of individualized interventions that simultaneously address time-varying needs across multiple socioecological levels (e.g. individual, interpersonal, community, structural and societal). Conclusion: Development of interventions to improve HIV testing rates and frequency of men who have sex with men has proliferated in recent years. Our review presents important implications in sustaining and improving interventions to address HIV testing uptake among men who have sex with men in the United States.